1985
DOI: 10.1007/bf00205686
|View full text |Cite
|
Sign up to set email alerts
|

Skin tests with autologous cholesteryl hemisuccinate treated tumour cells in cancer patients

Abstract: Skin tests with autologous irradiated tumour cells were performed in 20 malignant melanoma, 7 breast and 6 ovarian cancer patients. In the majority of cases evident reaction was noted with cholesteryl hemisuccinate (CHS)-treated cells while the reaction with untreated cells was mostly negative. No correlation was found between this reactivity and the ability of patients to be sensitized to DNCB and to their reactivity to PPD. No correlation was found between reactivity to CHS-treated tumour cells and the stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

1987
1987
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…The results presented here clearly show an enhanced delayed cutaneous hypersensitivity response in 54% of the patients who received irradiated autolo gous tumor cells from renal carcinoma pretreated with cholesteryl hemisuccinate compared to untreated cells. However, this ratio is lower than that reported by Skornick et al [12,13] or Munzarova et al [14], who observed strong skin reactions in 70% and 85% of the patients who had been tested in conditions similar to ours with autologous cholesteryl-hemisuccinate-treated tumor cells isolated from breast, ovary, gastric or colon carcinoma. No skin reaction with normal cells (circulat ing lymphocytes) or cholesteryl hemisuccinate suspen sion has been obseryed by these authors.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…The results presented here clearly show an enhanced delayed cutaneous hypersensitivity response in 54% of the patients who received irradiated autolo gous tumor cells from renal carcinoma pretreated with cholesteryl hemisuccinate compared to untreated cells. However, this ratio is lower than that reported by Skornick et al [12,13] or Munzarova et al [14], who observed strong skin reactions in 70% and 85% of the patients who had been tested in conditions similar to ours with autologous cholesteryl-hemisuccinate-treated tumor cells isolated from breast, ovary, gastric or colon carcinoma. No skin reaction with normal cells (circulat ing lymphocytes) or cholesteryl hemisuccinate suspen sion has been obseryed by these authors.…”
Section: Discussioncontrasting
confidence: 52%
“…Secondly, although we improved our methods to obtain cell preparations with a high percentage of viability, we cannot affirm that our cell suspension was cytologically pure. This problem was already evoked elsewhere [14]. A third possible explana tion for the relative low proportion of delayed cutaneous hypersensitivity responses we obtained with renal cancer cells consists in the improper physicochemical proper ties of their plasma membrane.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations